Teachers, arts practice and pedagogy - Franks, Anton; Thomson, Pat; Hall, Chris; Jones, Ken (Taylor & Francis, 2014)
What are possible overlaps between arts practice and school pedagogy? How is teacher subjectivity and pedagogy affected when teachers engage with arts practice, in particular, theatre practices? We draw on research conducted into the Learning Performance Network (LPN), a project that involved school teachers working with the Royal Shakespeare Company and the University of Warwick. The aim of the commissioned research was to look at the effects on teacher development, focusing on the active rehearsal room pedagogic techniques and ensemble methods of exploring Shakespearean text and performance. The practices of working as an ensemble through rehearsal room pedagogy were central to the LPN. Our interest is in looking for possible shifts in teachers’ subjectivity, their self-perception. What affordances, limitations, accommodations and tensions are experienced by the teachers in transposing work from the rehearsal room to the classroom? We draw on a range of cultural theories that provide complementary perspectives on aspects of subjectivity; these include Vygotskian approaches to the psychology of art and acting. Raymond Williams’s work on the ‘dramatized society’ and Jacques Rancière’s work on spectatorship and pedagogy. Data in the form of excerpts from field notes, taken in an introductory workshop where teachers worked with theatre practitioners, and from transcribed interviews with participants in the project are used to provide evidence of shifts in perspective, self-perception and pedagogic practice.